Comparison of Photoacoustically Derived Hemoglobin and Oxygenation Measurements with Contrast-Enhanced Ultrasound Estimated Vascularity and Immunohistochemical Staining in a Breast Cancer Model. (January 2015) - Eisenbrey, John R.; Merton, Daniel A.; Marshall, Andrew; Liu, Ji-Bin; Fox, Traci B.; Sridharan, Anush; Forsberg, Flemming
In this preliminary study, we compared two noninvasive techniques for imaging intratumoral physiological conditions to immunohistochemical staining in a murine breast cancer model. MDA-MB-231 tumors were implanted in the mammary pad of 11 nude rats. Ultrasound and photoacoustic (PA) scanning were performed using a Vevo 2100 scanner (Visualsonics, Toronto, Canada). Contrast-enhanced ultrasound (CEUS) was used to create maximum intensity projections as a measure of tumor vascularity. PAs were used to determine total hemoglobin signal (HbT), oxygenation levels in detected blood (SO2 Avg), and oxygenation levels over the entire tumor area (SO2 Tot). Tumors were then stained for vascular endothelial growth factor (VEGF), cyclooxygenase-2 (Cox-2), and the platelet endothelial cell adhesion molecule CD31. Correlations between findings were analyzed using Pearson's coefficient. Significant correlation was observed between CEUS-derived vascularity measurements and both PA indicators of blood volume ( r = 0.49 for HbT, r = 0.50 for SO2 Tot). Cox-2 showed significant negative correlation with SO2 Avg ( r = −0.49, p = 0.020) and SO2 Tot ( r = −0.43, p = 0.047), while CD31 showed significant negative correlation with CEUS-derived vascularity ( r = −0.47, p = 0.036). However, no significant correlation was observed between VEGF expression and any imaging modality ( p > 0.08). Photoacoustically derived HbT and SO2 Tot may be a good indicator of tumor fractional vascularity. While CEUS correlates with CD31 expression, photoacoustically derived SO2 Avg appears to be a better predictor of Cox-2 expression.